Learning through storytelling in higher education : using reflection & experience to improve learning - McDrury, Janice, 1949- (Kogan Page, 2003)
Learning Through Storytelling in Higher Education explores ways of using storytelling as a teaching and learning tool. When storytelling is formalized in meaningful ways, it can capture everyday examples of practice and turn them into an opportunity to learn - encouraging both reflection, a deeper understanding of a topic and stimulating critical thinking skills. The technique can accommodate diverse cultural, emotional and experiential incidents, and may be used in many different contexts eg formal/informal; one-on-one/group setting. The authors outline the different models of sto.